Quinoxalinophenanthrophenazine based cruciforms - Ueberricke, Lucas; Mizioch, Dennis; Ghalami, Farhad; Mildner, Felix; Rominger, Frank; Oeser, Thomas; Elstner, Marcus; Mastalerz, Michael (European journal of organic chemistry, 2021)
A series of cruciform aryl-substituted quinoxalinophenanthrophenazine derivatives (QPPs) was synthesized through Suzuki-Miyaura cross-coupling of a 2,7-diborylated pyrene tetraketal building block. The QPPs were analyzed for their optoelectronic properties by absorption and emission spectroscopy, cyclic voltammetry and quantum-chemical calculations. The solid-state packing was investigated as well and evaluated for its charge transport properties by calculated charge transfer integrals.